Diffuse Mesangial Sclerosis in a Child With Dyskeratosis Congenita Leading to End-stage Renal Disease (Iranian Journal of Kidney Diseases, 2016)
Dyskeratosis congenita (DC) is a very rare inherited disorder. It is caused by dysfunction of telomere maintenance. It involves RNA telomerase components relevant to various mutations leading to a classic triad of physical findings consisting of nail dystrophy of the hands and feet, mucosal leukoplakia, and reticular pigmentation of the skin, most commonly on the head, neck, and trunk. Bone marrow failure along with pulmonary complications and malignancies are all common causes of premature death in patients with DC as well as other abnormalities. We report a new case of DC with impure nephrotic syndrome relevant to histopathologic signs of a diffuse mesangial sclerosis, leading to an early end-stage renal disease. Challenges remain to understand the diverse spectrum of DC especially in children. To the best of our knowledge this is the first case of DC associated to diffuse mesangial sclerosis.